Principles of Broadband Switching and Networking. - Liew, Soung C. (John Wiley & Sons, 2008)
An authoritative introduction to the roles of switching and transmission in broadband integrated services networks. Principles of Broadband Switching and Networking explains the design and analysis?of switch architectures suitable?for broadband?integrated services networks, emphasizing packet-switched interconnection networks with?distributed routing?algorithms.?The?text examines the?mathematical properties of these networks, rather than?specific implementation technologies.?Although the pedagogical explanations?in this book are in the context?of switches, many of the fundamental principles?ar.